Applications of a microplate reader in yeast physiology research - Maresová, Lydie; Sychrová, Hana (BioTechniques, 2007)
Microplate readers have been useful assistants of researchers for several decades. This work is focused on the applications of a simple absorbance microplate reader in yeast physiology research, and its advantages and limitations in comparison with alternative methods are discussed. The two main procedures involved are measuring growth curves and monitoring the pH changes of medium using two different pH indicators. We suggest mathematical formulas for converting absorbance data into pH values. With a microplate reader as many as 96 samples can be simultaneously analyzed, while medium consumption is minimized to 100 microL per sample. The results can be observed in 24-48 h (for growth curves) or in 1-3 h (for pH changes) with minimal hands-on time required.
Keywords: fotometrie; Saccharomyces cerevisiae; kultivační média; Bromcresol Purple; Culture Media; Acids; bromkresolová zeleň; Photometry; koncentrace vodíkových iontů; Bromcresol Green; kalibrace; bromkresolová červeň; Calibration; kyseliny; Hydrogen-Ion Concentration